Firing Patterns of Leech Heartbeat Interneurons Under External Current Stimulation: a Model Study - Ju, N.; Liu, Sh.Q.; Lu, B.; Jiang, X. (Нейрофизиология, 2015)
Leech heartbeat interneurons (HN cells) interconnected by inhibitory synapses have been simulated using several modified models based on the Hodgkin-Huxley equations; yet, adequate characteristics of HN cells are hardly possible to be summarized due to the complexity of these models. The Winnerless Competition (WLC) model created as an inhibitory-connected nervous network is more appropriate for networks consisting of HN cells. We investigated different firing patterns produced by such model under application of various stimuli simulating changes in the leech’s environment. By means of recording the firing frequency, synchronization, interspike intervals (ISIs), and maxima of action potentials (APs) and also by application of the theory of mixed-mode oscillations (MMOs), different properties of firing patterns in HN cells were examined. According to the results of computational analyses, DC and AC stimulations were found to play different roles in modulating the leech’s heartbeat rhythm; external stimuli could influence the intensity and duration of the network reaction by changing both AP frequency and amplitude. Besides, changes in the recovery abilities of neurons can lead to various release modes of HN cells. Combined with physiological experiments on medical leeches, numerical analysis allows us to gain a deeper understanding of how HN cells coordinate with each other to bring the rhythm to the leech heartbeat system.